How the experience of medical trauma shapes Australian non-vaccinating parents' vaccine refusal for their children: A qualitative exploration - Maria Christou-Ergos; Julie Leask; Kerrie E. Wiley (Elsevier, 2022)
Vaccination decisions can be influenced by individuals' own, and others' experiences within the medical setting, as well as their relationship with providers and the broader medical system. However, is not clear how traumatic medical experiences interact with this relationship. We used grounded theory methodology to explore the role of medical trauma in shaping non-vaccinating parents' decision to refuse vaccination for their children. Twenty-two semi-structured interviews were conducted across Australia between September 2017 and February 2019. The inductive analysis found common narrative descriptions of negative medical experiences that contributed to vaccine hesitancy and/or refusal. A unique contribution of our study is the observation that negative experiences within the medical setting can be traumatic for individuals with consequences extending beyond the event to affect perceptions and relationships within the broader medical establishment. We observed that a negative medical event can set off a process with or without relational disruption that may influence subsequent thoughts and feelings, coping strategies, and for some parents, a re-evaluation of their vaccination decisions. We suggest that vaccination interventions may benefit from a better understanding of parents' past medical experiences and incorporate attempts to minimise personal and relational distress through individualised engagement and empathic communication before, during and after vaccination procedures.